Analysis of the present situation in tourism in two european regions: Pardubice and Brasov - Fratu, Delia; Brychtová, Šárka (Univerzita Pardubice, 2011)
This paper is aimed at analysing the tendencies in tourism over the past ten years in Pardubice and Brasov Regions, observing the differences and similarities and finding some viable solutions for these two Regions to become successful tourism destinations in the future.
Keywords: tourism trends; tourism indicators; regional tourism; marketing of tourism